Proceedings of the 12th Annual International Conference on Mobile Computing and Networking 2006
DOI: 10.1145/1161089.1161117
|View full text |Cite
|
Sign up to set email alerts
|

Broadcast capacity in multihop wireless networks

Abstract: In this paper we study the broadcast capacity of multihop wireless networks which we define as the maximum rate at which broadcast packets can be generated in the network such that all nodes receive the packets successfully in a limited time. We employ the Protocol Model for successful packet reception usually adopted in network capacity studies and provide novel upper and lower bounds for the broadcast capacity for arbitrary connected networks. In a homogeneous dense network these bounds simplify to Θ(W/ max(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
121
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(129 citation statements)
references
References 36 publications
(62 reference statements)
8
121
0
Order By: Relevance
“…According to Assumption 3, SaN is indeed dense scaling [6], [14], [15], [21], [22], while PhN is an extended network [4], [5], [12], [23]- [25]. More discussions about two types of scaling networks can be found in Section II-B of our technical report [26].…”
Section: A Network Topologymentioning
confidence: 99%
“…According to Assumption 3, SaN is indeed dense scaling [6], [14], [15], [21], [22], while PhN is an extended network [4], [5], [12], [23]- [25]. More discussions about two types of scaling networks can be found in Section II-B of our technical report [26].…”
Section: A Network Topologymentioning
confidence: 99%
“…Keshavarz-Haddad et al [28] studied the broadcast capacity of an arbitrary network, and showed that the per-session broadcast capacity is only of Θ(1/n). Shakkottai et al [29] designed a novel routing scheme, called comb scheme, by which the per-session multicast throughput can be achieved of order Ω(…”
Section: Under Threshold-based Channel Modelmentioning
confidence: 99%
“…The selection which nodes should forward the data and which should only receive it is a challenging task. A few algorithms have been proposed in the literature, however previous papers refer to a simple topologies with small average number of neighboring nodes (2)(3)(4)(5). In wireless AMI networks the average number of nodes to which a node can communicate is considerably higher [8].…”
Section: Introductionmentioning
confidence: 99%
“…This algorithm is also very simple to implement but has disqualifying disadvantages: can be costly in terms of wasted bandwidth and can impose a large number of redundant transmissions. Flooding is also not practical in dense networks, as it greatly increases the required transmission time [4].…”
Section: Introductionmentioning
confidence: 99%